Experiences of staff providing specialist palliative care during COVID-19: a multiple qualitative case study. (June 2022) - Bradshaw, Andy; Dunleavy, Lesley; Garner, Ian; Preston, Nancy; Bajwah, Sabrina; Cripps, Rachel; Fraser, Lorna K; Maddocks, Matthew; Hocaoglu, Mevhibe; Murtagh, Fliss EM; Oluyase, Adejoke O; Sleeman, Katherine E; et al.
Summary: Objective: To explore the experiences of, and impact on, staff working in palliative care during the COVID-19 pandemic. Design: Qualitative multiple case study using semi-structured interviews between November 2020 and April 2021 as part of the CovPall study. Data were analysed using thematic framework analysis. Setting: Organisations providing specialist palliative services in any setting. Participants: Staff working in specialist palliative care, purposefully sampled by the criteria of role, care setting and COVID-19 experience. Main outcome measures: Experiences of working in palliative care during the COVID-19 pandemic. Results: Five cases and 24 participants were recruited (n = 12 nurses, 4 clinical managers, 4 doctors, 2 senior managers, 1 healthcare assistant, 1 allied healthcare professional). Central themes demonstrate how infection control constraints prohibited and diluted participants' ability to provide care that reflected their core values, resulting in experiences of moral distress. Despite organisational, team and individual support strategies, continually managing these constraints led to a 'crescendo effect' in which the impacts of moral distress accumulated over time, sometimes leading to burnout. Solidarity with colleagues and making a valued contribution provided 'moral comfort' for some. Conclusions: This study provides a unique insight into why and how healthcare staff have experienced moral distress during the pandemic, and how organisations have responded. Despite their experience of dealing with death and dying, the mental health and well-being of palliative care staff was affected by the pandemic. Organisational, structural and policy changes are urgently required to mitigate and manage these impacts.